Digital citizenship: an introduction to developing e-commerce competencies among students of commercial technical education. - Amr Toony Ali Al-kardousi; Burhamy Abd El- Hameed Zaghloul (International Journal of Advanced Humanities Research)
Digital citizenship is one of the modern concepts in educational literature in general, Digital citizenship aims to prepare students and improve appropriate and responsible behavior to use digital communication tools to become citizens capable of keeping pace with the twenty-first century, given that the competencies of e-commerce represent an important requirement of the labor market and one of the competencies that must be available to graduates of commercial technical secondary education, as it helped to provide a lot of job opportunities, reduce the unemployment rate, double productivity rates, and made an important role for its workers in the field of development. It is also a dimension of digital citizenship, and due to the lack of e-commerce competencies in commercial secondary education courses, appropriate research tools have been prepared for first-year commercial secondary students, which were represented in building a list of e-commerce competencies, knowledge testing, descriptive estimation guide, and the researcher also followed that in this research the semi-experimental design with one experimental group, With the application of beforeandafter the research tools, a study sample was formed from (30) students from the first grade of commercial secondary school at Badr Commercial Secondary School, and the tools were applied over a period of three months, the results of the study proved the effectiveness of digital citizenship as an input to the development of e-commerce competencies.